Functioning and equality according to International Classification of Functioning, Disability and Health (ICF) in people with skeletal dysplasia compared to matched control subjects – a cross-sectional survey study - Hyvönen, Hanna; Anttila, Heidi; Tallqvist, Susanna; Muñoz, Minna; Leppäjoki-Tiistola, Sanna; Teittinen, Antti; Mäkitie, Outi; Hiekkala, Sinikka (BMC musculoskeletal disorders, 2020)
Skeletal dysplasias are rare disorders often leading to severe short stature. This study aimed to gain new comprehensive information about functioning and equality in people affected by skeletal dysplasia compared to matched controls without skeletal dysplasia. Functioning was assessed by questionnaire, which was formed by operationalizing International Classification of Functioning, Disability and Health (ICF) core set's categories into the items according to the ICF linking rules, using primarily Patient Reported Outcomes Measurement Information System PROMIS® - items. Altogether 80 subjects with skeletal dysplasia and 55 age-, gender- and place of residence -matched controls participated. People with skeletal dysplasia experienced more pain (p < 0.001) and the pain interfered more their daily lives (p = 0.037) compared to the controls. They had more problems related to musculoskeletal functions and exercise tolerance, difficulties in mobility, used more assistive products and technology and were more affected by climate and seasonal changes (p < 0.001). They met challenges in self-care, acquisition of goods and services and household tasks (p < 0.001) and in participating in close social relationships, leisure time activities (p < 0.001) and associations and organizational services (p = 0.007). They felt less satisfied with remunerative work (p = 0.003), felt more inequality (p = 0.008), met more negative attitudes of others (p < 0.001) and felt having less support given by family and friends (p = 0.022). They used more social and health services and experienced more dissatisfaction with those. Our study indicates that skeletal dysplasias restrict functioning extensively and significantly affect daily living. By building accessible environment and improving equal services, functioning could be improved.